2020
DOI: 10.21203/rs.3.rs-36965/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High HbA1c is associated with decreased 6-month survival and poor outcomes after out-of-hospital cardiac arrest: a retrospective cohort study

Abstract: Background: To evaluate the associations between glycated hemoglobin (HbA1c) at admission and 6-month mortality and outcomes after out-of-hospital cardiac arrest (OHCA) treated by hypothermic targeted temperature management (TTM).Methods: This single-center retrospective cohort study included adult OHCA survivors who underwent hypothermic TTM from December 2011 to December 2019. High HbA1c at admission was defined as a level higher than 6%. Poor neurological outcomes were defined as cerebral performance catego… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The relationship between a patient's glucose level and outcomes has been studied in previous studies [19][20][21][22]. Additionally, HbA1c was analyzed in patients treated with TTM after OHCA [34,39]. We classified patients previously diagnosed with diabetes into four groups: those with controlled diabetes, inadequately controlled diabetes, unrecognized diabetes, and no diabetes with adequate glucose control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between a patient's glucose level and outcomes has been studied in previous studies [19][20][21][22]. Additionally, HbA1c was analyzed in patients treated with TTM after OHCA [34,39]. We classified patients previously diagnosed with diabetes into four groups: those with controlled diabetes, inadequately controlled diabetes, unrecognized diabetes, and no diabetes with adequate glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical guidelines generally advocate for an HbA1c threshold of �6.5% for diagnosing diabetes and a range of 5.7 to 6.4% for identifying prediabetes. However, Silverman et al have suggested that in acute-care settings such as emergency departments, an HbA1c of 5.7% is the optimal screening cutoff for prediabetes, while 6% is optimal for diagnosing diabetes [33,34]. Consequently, we established a cutoff value of HbA1c at 6.0% to assess the adequacy of glucose control and diagnose diabetes.…”
Section: Glucose Management Protocolmentioning
confidence: 99%